GLP-1 RA for cardiometabolic risk reduction in obesity - How do we best describe benefit and value? - Sant Kumar; Michael J. Blaha (Elsevier, 2024)
How do we assess the overall benefit and value of GLP1-RAs? Current clinical trials often focus narrowly on individual atherosclerotic cardiovascular endpoints like MACE, potentially missing broader GLP-1 RA benefits across multiple comorbidities. Herein, we set out a framework for expanding outcome analyses in large trials that we believe will provide a more holistic understanding of GLP-1 RA benefits across the cardio-kidney-metabolic (CKM) spectrum, guiding patient care, guidelines, and insurance coverage decisions.